Removal of Organic Pollution in Water Environment - Kotowska, Urszula (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The development of civilization entails a growing demand for consumer goods. A side effect of the production and use of these materials is the production of solid waste and wastewater. Municipal and industrial wastewater usually contains a large amount of various organic compounds and is the main source of pollution of the aquatic environment. Therefore, the search for effective methods of wastewater and other polluted water treatment is an important element of caring for the natural environment. This book presents research on the determination and removal of environmentally hazardous organic compounds from aqueous samples. The articles included in this book describe the results of examinations, at the laboratory scale, of the efficiency of chemical as well as physical processes for the removal or degradation of selected model pollutants. Environmental studies, especially those concerning the determination of trace impurities, require effective isolation and concentration procedures. The methods used for this purpose should meet the requirements of green chemistry. The liquid phase microextraction procedures and use of electrochemical methods described in this book seem to be proper for environmental studies, as they are effective and environmentally friendly.